Penerapan Metode Pembelajaran Diskusi Dan Resitasi Dalam Meningkatkan Hasil Belajar Pendidikan Agama Hindu Siswa Kelas Iv Sd Negeri 2 Tumbu Karangasem - Ida Ayu Putu Suci Lestari (Jurnal Penjaminan Mutu, 2018)
This study aims: (1) to know the application of the use of methods of discussion and recitation can improve the learning outcomes of Hindu religious education fourth graders Elementary School 2 Tumbu. (2) to find out constraints faced in using the method of assignment and recitation in the learning of Hindu religious education fourth grade students of SD Negeri 2 Tumbu. The type of this research is Classroom Action Research (PTK) with the subject of this research is the fourth grader of SD Negeri 2 Tumbu, the Hindu of 17 people from 22 students, consist of 10 men, and 7 women. The research was conducted at SD Negeri 2 Tumbu Karangasem. This research was conducted in two cycles. One cycle consists of preparation, execution, observation and reflection. Data collection is done by test method. Then the data is analyzed by quantitative descriptive technique. The results of this study is an increase in learning outcomes, the initial reflection of the average learning outcomes of Hindu religious education amounted to 54.7 with 29,41% complete learning. Then, in the first cycle the average learning outcomes of Hindu religious education increased to 69.4 and the classical completeness of 64.71% is still less than the classical completeness set 85%. Thus, learning in cycle I has not been completed. In cycle II the average learning outcomes of Hindu religious education increased to 79.1 and 100% classical completeness, thus the learning cycle II completed.